Gambaran Implementasi Pengembangan Keprofesian Berkelanjutan oleh Perawat di RSUD R.A. Kartini Kabupaten Jepara - Madya Sulisno; Agus Santoso; Bambang Edy Warsito; Luthfi Hidayah; Sarah Ulliya; Muhammad Hasib Ardani; Muhamad Rofii (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2021)
Introduction: Continuing Professional Development (CPD) implementation is not optimal. There is no evaluation regarding CPD implementation by nurses in RSUD R.A. Kartini, Jepara Regency. The purpose of this study was to describe the implementation of PKB by nurses in RSUD R.A. Kartini, Jepara Regency.Methods: This study used quantitative research design using descriptive studies. The sampling technique used simple random sampling with 169 respondents. Data collection used a questionnaire containing 55 question items from Indonesian National Nurses Association.Results: Description of CPD by nurses at R.A. Kartini Hospital in Jepara Regency are as follows: professional practice activities (100%), scientific activities (94.67%), scientific development activities (26.62%), and community service activities (71%). Conclusion: Based on the research results, nurses should optimize themselves in various aspects of the form of CPD activities so that it can fulfill the achievement of 25 credits in five years while increasing the self-development of nurses.